Food consumption and undernutrition variations among mothers during the post-harvest and lean seasons in Amoron'i Mania Region, Madagascar - Lantonirina Ravaoarisoa; Julio Rakotonirina; Lalhyss Randriamanantsaina; Jean de Dieu Marie Rakotomanga; Michèle Wilmet Dramaix; Philippe Donnen (BMC Public Health, 2019)
Abstract Background Seasonal variation affects nutrition particularly in contexts where people’s food consumption depends on their production of food. Assessing the effect of the season on nutrition status can help us to identify strategies to address undernutrition. This study aims to measure the variations in food consumption and the incidence of undernutrition according to season, and to identify the factors associated with the incidence of undernutrition. Methods A cohort study was conducted among 608 mothers aged between 18 and 45 years living in the Amoron’i Mania Region of Madagascar. Inclusion in the study occurred during the post-harvest season, and mothers were followed until the end of the next lean period (7 months). A dichotomous variable of the frequency of consumption of various foods was used to establish variation in food consumption. Body Mass Index < 18.5 kg/m2 and Middle Upper Arm Circumference < 220 mm were used to measure incidence of undernutrition. A generalized linear model was used to identify factors associated with the incidence of undernutrition and to derive relative risks. Results During the lean season, the frequency of consumption of leafy green vegetables, peanuts, fish, and eggs decreased significantly. In contrast, the frequency of fruit, legumes, and non-leafy green vegetables consumption increased significantly. The prevalence of undernutrition (based on the BMI and/or MUAC) among mothers increased from 19.6% in the post-harvest period to 27.1% in the lean period (p < 0.001). The incidence of undernutrition (based on the BMI and/or MUAC) during the follow-up was 12.2%. The factors related to undernutrition were low and medium score of movable property possession (Adjusted RR = 3.26 [1.33–7.94] and Adjusted RR = 2.48 [1.01–6.10]), no toilet (Adjusted RR = 1.76 [1.07–2.91]), and pregnancy (Adjusted RR = 2.92 [1.42–6.04]) (based on the MUAC only for pregnancy). Conclusion This study highlights the variation in the frequency and type of food consumption and subsequent deterioration in mothers’ nutritional status during the lean season. Economic, hygiene, and reproductive factors were associated with undernutrition. Analyzing the existing interventions to fight maternal undernutrition is necessary to determine whether or not seasonality is considered and addressed.